Studies on the Susceptibility of Granular Cassava and Com Starches to Enzymatic Attack Part I: Study of the Conditions of Hydrolysis - Franco, Célia M. L. [UNESP]; Preto, São José Dorio; Ciacco, C. F. (My University, 1987)
In this research, the susceptibility of starch granules to enzymatic hydrolysis was studied. Cassava and corn starches were hydrolysed by bacterial α‐amylase with and without amyloglucosidase under several conditions of incubation. The highest percentage of hydrolysis was obtained in the presence of both enzymes. Elimination of the soluble hydrolysis products by dialysis increased the degradation of the starch granules, especially with cassava starch. Copyright © 1987 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim